2018
DOI: 10.1136/bmjopen-2017-020972
|View full text |Cite
|
Sign up to set email alerts
|

Glycated haemoglobin A1c(HbA1c) for detection of diabetes mellitus and impaired fasting glucose in Malawi: a diagnostic accuracy study

Abstract: ObjectivesTo examine the accuracy of glycated haemoglobin A1c (HbA1c) in detecting type 2 diabetes and impaired fasting glucose among adults living in Malawi.DesignA diagnostic validation study of HbA1c. Fasting plasma glucose (FPG) ≥7.0 mmol/L was the reference standard for type 2 diabetes, and FPG between 6.1 and 6.9 mmol/L as impaired fasting glucose.Participants3645 adults (of whom 63% were women) recruited from two demographic surveillance study sites in urban and rural Malawi. This analysis excluded thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
(28 reference statements)
1
14
1
Order By: Relevance
“…HbA 1c had a sensitivity of 78.7% and specificity of 94.0% to detect FPG-diagnosed diabetes. 22 The high HbA 1c specificity in both of these studies relative to our study may be partly attributable to the age-dependent relationship between HbA 1c and FPG, with HbA 1c increasing in older people independent of glycaemia. 23 A second important difference is the lower BMI (median 22.6 kg/m 2 ) in the Malawian study, given higher BMI is also associated with higher HbA 1c independent of glycaemia.…”
Section: Discussioncontrasting
confidence: 45%
“…HbA 1c had a sensitivity of 78.7% and specificity of 94.0% to detect FPG-diagnosed diabetes. 22 The high HbA 1c specificity in both of these studies relative to our study may be partly attributable to the age-dependent relationship between HbA 1c and FPG, with HbA 1c increasing in older people independent of glycaemia. 23 A second important difference is the lower BMI (median 22.6 kg/m 2 ) in the Malawian study, given higher BMI is also associated with higher HbA 1c independent of glycaemia.…”
Section: Discussioncontrasting
confidence: 45%
“…Recent studies examining the relation between HbA 1c and anaemia have generally focused on anaemia classified solely using haemoglobin levels, or iron-deficiency anaemia (defined using additional measures including ferritin and transferrin)-which commonly causes microcytic anaemia 9,16,[20][21][22] [S3-S5]. The majority of these studies have reported inverse associations or correlations between HbA 1c levels and such measures that are generally small in magnitude 9,16 [S3, S4].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, few studies have been based in African populations, with mixed evidence regarding the presence, direction and magnitude of associations between anaemia and HbA 1c . [20][21][22] This points to the need for further, comprehensive evidence from this region. The exact mechanisms by which different types of anaemia may affect HbA 1c are not clear, with multiple proposed hypotheses regarding pathways.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 In contrast, Rathod et al, in their study conducted in Malawi, concluded that HbA1c as a stand-alone test was highly predictive for diagnosis of type 2 DM but less so for impaired fasting glucose. 14 Other studies from Uganda and South Africa, like those done in East Asia, Europe and the Middle East, have demonstrated that HbA1c is an effective test for DM detection across various ethnic groups. 13,[15][16][17][18] Results from a metanalysis of studies conducted in 38 countries found that HbA1c had a high specificity but a low-to-moderate sensitivity for detection of DM.…”
Section: Introductionmentioning
confidence: 95%